Substrate availability and not thermal acclimation controls microbial temperature sensitivity response to long‐term warming - Luiz A. Domeignoz‐Horta; Grace Pold; Hailey Erb; David Sebag; Eric Verrecchia; Trent Northen; Katherine Louie; Emiley Eloe‐Fadrosh; Christa Pennacchio; Melissa A. Knorr; Serita D. Frey; Jerry M. Melillo; et al. (Global Change Biology, 2023)
Microbes are responsible for cycling carbon (C) through soils, and predicted changes in soil C stocks under climate change are highly sensitive to shifts in the mechanisms assumed to control the microbial physiological response to warming. Two mechanisms have been suggested to explain the long‐term warming impact on microbial physiology: microbial thermal acclimation and changes in the quantity and quality of substrates available for microbial metabolism. Yet studies disentangling these two mechanisms are lacking. To resolve the drivers of changes in microbial physiology in response to long‐term warming, we sampled soils from 13‐ and 28‐year‐old soil warming experiments in different seasons. We performed short‐term laboratory incubations across a range of temperatures to measure the relationships between temperature sensitivity of physiology (growth, respiration, carbon use efficiency, and extracellular enzyme activity) and the chemical composition of soil organic matter. We observed apparent thermal acclimation of microbial respiration, but only in summer, when warming had exacerbated the seasonally‐induced, already small dissolved organic matter pools. Irrespective of warming, greater quantity and quality of soil carbon increased the extracellular enzymatic pool and its temperature sensitivity. We propose that fresh litter input into the system seasonally cancels apparent thermal acclimation of C‐cycling processes to decadal warming. Our findings reveal that long‐term warming has indirectly affected microbial physiology via reduced C availability in this system, implying that earth system models including these negative feedbacks may be best suited to describe long‐term warming effects on these soils.